Domestication De Thunbergia Atacorensis Akoegninou & Lisowski (Acanthaceae) : Effet Du Type De Substrat Et Du Mode D’eclairement Sur L’aptitude A La Reprise Vegetative Des Boutures Et La Croissance Des Plants - Estelle, Asseh Ebah; Emma, Ake-Assi; Jean, Koffi Kouao; Faustine, Kouassi Akossoua; Edouard, N’guessan Kouakou (European Scientific Journal, ESJ, 2017)
We studied the possibility of producing seedlings of Thunbergia atacorensis (Acanthaceae) starting from cuttings under controlled cultivation conditions during 3 months. The objective of this work is to determine the optimal conditions for seedling production Thunbergia atacorensis by vegetative reproduction to allow its extension from professional growers and amateur (consumers). The study consisted to analyze their effect the plant growth, seedlings development, and leaves production. At the end the study, we obtained a rate of 91p.c for vegetative recovery for the cutting in shade 97p.c. for the cutting exposing to sun. However, the cuttings exposed sun clearly dissociates cuttings exposed to the shade with a shorter time of recovery. At the end of 3 months, only the sunny seedlings survive despite of the recovery rate of recovery. The study showed that the four environmental factors, the mode of exposure (sun and shade) and time (weeks) have a significant influence on the height and the number of seedlings leaves. The highest seedlings are observed in the shade from weeks 1 to 3. From week 3, only the sunny seedlings continue their growth and their development. The variation of the substrate and the frequency of watering, meanwhile, had no significant influence on the height and number of leaves. In sum, despite of lack of flowering, to produce seedlings of Thunbergia atacorensis, one should initially carry out the propagation by cutting in the shade and then to gradually intensify the light to have well developed seedlings.